Oversigt over undersøgelser og forsøg vedrørende fluebekæmpelsen 1949. - Højgaard Olsen, N. J. (Tidsskrift for Landøkonomi, 2018)
Oversigt over undersøgelser og forsøg vedrørende fluebekæmpelsen 1949.